Cyclopentannulated dihydrotetraazapentacenes [data] - Maier, Steffen; Heckershoff, Robin; Wurm, Thomas; Biegger, Philipp; Brödner, Kerstin; Krämer, Petra; Hoffmann, Marvin; Eberle, Lukas; Stein, Jana; Rominger, Frank; Rudolph, Matthias; Freudenberg, Jan; et al. (Universität, 2022)
The transition-metal catalyzed cyclization of bissilylethynylated N,N’-dihydro¬tetra¬aza¬pentacene (TIPS-TAP-H2) into bissilylated cyclo¬penta¬[fg,...
Gesehen am 15.12.2022
Keywords: Forschungsdaten; Datenbank